Torsional path integral Monte Carlo method for calculating the absolute quantum free energy of large molecules - Miller, T; Clary, D (2003)
The torsional PIMC technique for the calculation of the absolute free energy is introduced and applied to the molecules ethane, n-butane, n-octane, and enkephalin. The quantum contributions to torsional degrees of freedom are treated in a fashion that converges systematically to the exact result. Utilization of a novel importance sampling distribution based on a model system of uncoupled free rotors and harmonic oscillators enables direct evaluation of the molecular partition function from which free energy is obtained. Calculations indicate that the quantum contributions to free energy are quite significant. A comparison of the TPIMC technique with the harmonic oscillator approximation and a variational technique is performed for the ethane molecule, and only the TPIMC technique is found to be applicable to large molecular systems.